Effects of isotretinoin on body mass index, serum adiponectin, leptin, and ghrelin levels in acne vulgaris patients - Cemil, Bengu Cevirgen; Ayvaz, Havva Hilal; Ozturk, Gulfer; Ergin, Can; Akıs, Havva Kaya; Gonul, Muzeyyen; Arzuhal, Ercan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Isotretinoin has been successfully used for the treatment of acne vulgaris. Aim : To investigate the effects of isotretinoin on body mass index (BMI), to determine whether isotretinoin causes any changes in serum adiponectin, leptin, and ghrelin levels in acne vulgaris patients, and to correlate variables. Material and methods: Thirty-two patients were included in this study. Oral isotretinoin was begun at a dose of 0.5–0.6 mg/kg and raised to 0.6–0.75 mg/kg. Pretreatment and posttreatment third-month BMI and adiponectin, leptin, and ghrelin serum levels were measured. Results : The pre- and posttreatment BMI values were not significantly different. In addition, serum adiponectin and leptin levels were significantly increased following isotretinoin therapy while serum ghrelin levels were not different. Conclusions : Isotretinoin may exert its anti-inflammatory activity by increasing leptin and adiponectin levels.